Kepuasan Konsumen Sunyi House of Coffee and Hope - Lorenssa, Berliana Adinda; Astuti, Miguna; Husniati, Renny (Jurnal Ilmiah Manajemen Kesatuan, 2020)
In this research there is a quantitative descriptive methods were used with respondents, namely consumers of Sunyi House of Coffee and Hope. This coffee shop has employees with disabilities. In this research aims to determine the condition of consumer satisfaction Sunyi House of Coffee and Hope is influenced by the service quality, location and facilities. The population in this study are customers of Sunyi House of Coffee and Hope. Samples taken as many as 100 respondents by random sampling method. Data collection was done through the distribution of questionnaires with descriptive data analysis techniques. The results of the study stated that 1). Has led to customer satisfaction Sunyi House of Coffee and Hope, 2). Service quality has been done well, 3). The location offered received very high attention, 4). The facilities provided are quite good. Keywords : Service Quality, Location, Facilities, Customer Satisfaction, Coffee Shop